Stabilizing asset prices through transition from continuous trading to electronic auctions - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2023)
The paper deals with the pattern of asset price dynamics as sequence of "bull markets" and "bear markets" and with stabilizing these" long swings" through replacing continuous asset trading with electronic auctions. First, the paper sketches the channels through which the "overshooting" of exchange rates, commodities prices, and stock prices but also of EU carbon prices dampens the real economy and hampers fighting global heating. Second, a theoretical alternative to the still dominating "efficient market hypothesis" is presented, the "bull-bearhypothesis". Third, the paper discusses the role of "technical" or "algorithmic" trading strategies in exploiting short-term asset price trends and strengthening them at the same time. Fourth, it is shown that bulls (bear) markets result from (verry) short-term trends ("runs") in line with the prevailing (bullish or bearish) market sentiment lasting longer than counter-movements. Fifth, to mitigate the extent of the "long swings" of asset prices one needs to restrict (super) fast speculation unrelated to market fundamentals thereby dampening the short-term trending of asset prices. Instead of implementing a financial transactions tax, one could achieve this objective also through replacing continuous trading with electronic auctions, e.g., every three hours. This approach is theoretically more appealing, technically easy to implement and has so far not seriously been discussed.
Keywords: D44; G12; G14; G41; 330; Asset price dynamics; technical or algorithmic trading